MHPSS - a resource for peace: Displacement situations, psychosocial support and the humanitarian-development-peace nexus - Nadine Biehler; Amrei Meier (Stiftung Wissenschaft und Politik (SWP), 2026)
Persons fleeing their homes are exposed not only to physical dangers but also to severe psychological distress - from the ordeal of displacement itself and the experience of violence to unsafe living conditions and a lack of any prospects at their destination. It is not just those directly involved who are affected by the consequences of such traumatic experiences; the social cohesion of societies and their economic development and stability are threatened, too. Both in the political discourse and in international aid programmes, mental health and psychosocial support (MHPSS) in displacement situations is often neglected. But MHPSS measures can have a positive social impact: on coexistence in the host countries and on peace processes in the countries of origin. Thus, they directly support the third dimension of the humanitarian-development-peace (HDP) nexus - the so-called peace pillar. The HDP nexus aims to link humanitarian aid and development to peacebuilding. Such efforts are particularly important in displacement situations.
Keywords: 320; displacement; humanitarian-development-peace (HDP) nexus; mental health and psychosocial support (MHPSS); peacebuilding; reintegration